1998
DOI: 10.1590/s0100-879x1998000600013
|View full text |Cite
|
Sign up to set email alerts
|

Opiatergic participation in the thirst-inhibiting effect of acute third ventricle injections of cadmium (Cd2+) and lead (Pb2+)

Abstract: We have previously demonstrated that acute third ventricle injections of both lead and cadmium prevent the dipsogenic response elicited by dehydration or by central injections of dipsogenic agents such as angiotensin II, carbachol and isoproterenol in rats. We have also shown that the antidipsogenic action of cadmium may be due, at least in part, to activation of thirst-inhibitory central serotonergic pathways. In the present paper we show that in Wistar male rats the antidipsogenic effect of both lead acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This thirst-inhibiting effect of central lead administration may be, at least in part, opioid-dependent, as we have also shown (8). Recently, we have demonstrated that central injection of lead, in the same amounts used to inhibit water intake, causes a significant increase in renal sodium and potassium excretion (9).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This thirst-inhibiting effect of central lead administration may be, at least in part, opioid-dependent, as we have also shown (8). Recently, we have demonstrated that central injection of lead, in the same amounts used to inhibit water intake, causes a significant increase in renal sodium and potassium excretion (9).…”
Section: Introductionsupporting
confidence: 57%
“…We have previously shown that lead injections into the third ventricle induce a significant antidipsogenic ef- fect in several physiological and pharmacological situations (6,7), an effect due, at least partially, to a stimulation of central opioid pathways (8). More recently, we have demonstrated that acute intracerebroventricular injections of lead induce a powerful natriuretic and kaliuretic effect (9).…”
Section: Introductionmentioning
confidence: 98%